The investigation of HLA microsatellites influence in predisposition to sarcoidosis among Croatians - Grubić, Z.; Peroš-Golubičić, T.; Štingl, et al., K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
The aim of the present study was to analyze the distribution of HLA alleles (A, B, DRB1, DQB1) and HLA microsatellite alleles (TNFa, TNFb, TNFd, D6S273, D6S1014) in the Croatian patients with acute (N=93), as well as chronic sarcoidosis (N=40), in comparison to healthy controls (N=177), and investigate whether the polymorphism within the HLA region could be associated with different forms of sarcoidosis. Genomic DNA was isolated from peripheral blood. Patients were analyzed for HLA class I loci (A, B) by serology, while PCR-SSP method was used for HLA class II loci (DRB1, DQB1). Five HLA microsatellites were analyzed by PCR and electrophoresis in an automated sequencer. No significant deviation in the distribution of frequencies at HLA class I alleles was observed between the two patients’ subgroups and controls. Regarding the HLA class II alleles, a statistically significant increase in frequency of HLA-DRB1*03 and DQB1*0201 allele was found among patients with acute sarcoidosis in comparison to controls as well as in comparison to patients with chronic sarcoidosis. The same finding was observed for HLA-DRB1*03/DQB1*0201 haplotype (Pcorr=0.0168; OR=2.83). In the group of patients with chronic sarcoidosis DRB1*11 (P=0.0219; OR=2.44), DRB1*15 (P=0.0414; OR=2.47) demonstrated statistically significant difference in comparison to controls only, while a lower frequency of DRB1*13 (P=0.0156; OR=0.24) in this group was statistically significant when compared to both patients with acute sarcoidosis and controls. None of the alleles at TNFa microsatellite showed significant difference in distribution among both subgroups of patients and controls. Significant difference between patients with acute form of disease and controls was found for the following alleles: TNFd-2 (Pcorr=0.00007; OR=4.89), D6S273-7 (Pcorr=0.0213; OR=2.96), and D6S1014-7 (Pcorr=0.0028; OR=3.97). On the other hand, patients with chronic sarcoidosis differed from control subjects for D6S1014-8 (Pcorr=0.0296; OR=8.35) allele. This study suggests the existence of an association of non-HLA markers with sarcoidosis and the involvement of the region between HLA-DQB1 and D6S273 loci in its pathophysiology.